2018
DOI: 10.5152/iao.2018.4929
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Molecular Biology of Sporadic Vestibular Schwannomas: A Systematic Review and Clinical Implications

Abstract: In light of missing systematic reviews in the literature, the objective of this paper is to present the contemporary knowledge on the molecular biology of vestibular schwannomas (VS), based on a systematic literature search. In addition, current and prospected medical therapy based on molecular biology is addressed. A systematic literature search was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The systematic search was performed in the Pubmed and Embase da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 76 publications
0
17
0
1
Order By: Relevance
“…To understand the mechanism, we wanted to evaluate whether there are any genetic aberrations associated with GKRS treatment resistance. Previous studies on structural changes in the VS genome have identified chromosome 22q loss as the only recurring event, present in 25-83% of VSs [12]. However, previous studies have used techniques with lower resolution.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the mechanism, we wanted to evaluate whether there are any genetic aberrations associated with GKRS treatment resistance. Previous studies on structural changes in the VS genome have identified chromosome 22q loss as the only recurring event, present in 25-83% of VSs [12]. However, previous studies have used techniques with lower resolution.…”
Section: Introductionmentioning
confidence: 99%
“…In a first study using human vestibular Schwannoma (VS) cells, AIT was found to negatively regulate miR‐21, which is an abundant microRNA, frequently expressed in cancer cells and upregulated in VS cells (Sass & Cayé‐Thomasen, 2018). It functions as an oncogene, acting as the regulator of programmed cell death 4 (PDCD4) by targeting its 3′‐untranslated region to promote tumor proliferation, migration, and invasion in different types of carcinoma (Zhao et al, 2019).…”
Section: Regulation Of Mi‐rnas Expression and Functionmentioning
confidence: 99%
“…Merlin gene silencing is a molecular feature shared by unilateral sporadic vestibular schwannomas and bilateral vestibular schwannomas associated with NF2. In sporadic cases, somatic bi-allelic merlin gene inactivation seems essential to tumor formation 9 . Merlin gene mutations consist of insertions, deletions, and single-base substitutions resulting in frameshifts and nonsense mutations.…”
Section: Advancements and Open Issuesmentioning
confidence: 99%
“…Merlin gene mutations consist of insertions, deletions, and single-base substitutions resulting in frameshifts and nonsense mutations. They mainly prompt the synthesis of truncated proteins 910 . NF2 gene inactivation results in total merlin loss, and has been detected in 27% to 61% cases of sporadic vestibular schwannoma 11 .…”
Section: Advancements and Open Issuesmentioning
confidence: 99%
See 1 more Smart Citation